An Empirical Analysis of Impact of XBRL on Quality of Financial Reporting in India - Abhishek, N (Technium EconomiA, 2024)
The efficient and effective communication of business and financial information to end-users helps to get clear insights on the business outlook and assists them in making timely decisions. Financial reporting acts as a vehicle to disseminate the financial information of the business to various interested parties by communicating operating and financial information through financial statements, notes to financial statements and other footnotes in the annual report. Nowadays stakeholders of the business are more expecting both financial and non-financial information to be communicated in a single annual report. Therefore, the corporate houses are required to communicate enhanced information in their annual reports to facilitate the stakeholders in their decision-making process. Communication of enhanced information in the annual report is only possible with the help of the EBR Model (Enhanced Business Reporting Model) which is only possible by the application of XBRL (Extensible Business Reporting Language) to the business reporting purpose. The present paper is intended to examine the impact of XBRL on the quality of financial reporting. For this purpose, the study analysed the financial reporting pattern of 23 select companies in India through the analysis of their annual reports from 2005 to 2020. To derive valid conclusions Tukey test, dummy variable regression analysis techniques were employed and concluded that XBRL has made a significant impact on the quality of financial reporting of select companies.